Malaysian adolescents’ moral awareness and cultural conformity : some implications for today’s educational management - Abd Hamid, Siti Rafiah; Nik Abdul Rahman, Nik Suryani; Ismail, Khamsiah; Rais, Haniza (International Institute of Islamic Civilisation and Malay World (ISTAC), 2018)
It has been reported in printed and electronic media that moral decadency among Malaysian adolescents is on the rise. Such decadency is attributed by a host of “nature versus nurture” debatable factors. This study aims at describing the moral awareness and cultural conformity of Malaysian adolescents. A questionnaire was administered on 200 respondents. Preliminary findings indicated that the respondents’ conformed positively to their cultural expectations (M= 3.92; SD= .92) and have positive moral awareness is (M = 4.40; SD = .85). These findings were perceived instrumental to the current classroom managements, school counseling services and choice of parenting styles in Malaysia.